PENGARUH ATRIBUT PRODUK DAN SEGMENTASI PASAR TERHADAP MINAT BELI DEPOSITO PT BANK DBS INDONESIA, TBK KCP DIPONEGORO MEDAN - Fera Fera; Syawaluddin Syawaluddin; Mila Asmawiani Okta (JURNAL BISNIS KOLEGA, 2021)
This research was conducted at PT Bank DBS Indonesia, Tbk KCP Diponegoro Medan. The purpose of this study was to determine and analyze the influence of Product Attributes and Market Segmentation on Deposit Purchase Interest of PT Bank DBS Indonesia, Tbk KCP Diponegoro Medan. The population numbered 126 customers while the sample in this study were: which amounted to 96 customers. The sampling technique used is simple random sampling. Data collection techniques are by distributing questionnaires, interviews and documentation studies. Data analysis uses multiple linear regression analysis.The conclusion in the study that simultaneously Product Attributes and Market Segmentation has a positive and significant effect on Interest in Buying Deposits of PT Bank DBS Indonesia, Tbk Diponegoro KCP Medan. Partially Product Attributes have a positive and significant effect on PT Bank DBS Indonesia, Tbk KCP Diponegoro Medan Deposit Interests. Partially Market Segmentation has a positive and significant effect on PT Bank DBS Indonesia, Tbk KCP Diponegoro Medan Deposit Interests. The magnitude of the coefficient of determination seen from the Adjusted R Square value is: equal to 0.574 means that Product Attributes and Market Segmentation can explain Purchase Interest by 57.4% and the remaining 42.6% is influenced by other variables outside of this study such as: advertising, service quality, personal selling and so on.Â Â Keywords: Product Attributes, Market Segmentation, Purchase Interest